Foreign Reserves of the Iraqi Central Bank's and its influence on Foreign Investment flows - BniLam, Dr. Ali H. N. (Technium Business and Management, 2022)
variable, which is foreign investment in an unstable environment that has not been witnessed by any country in the world. And because the research is applied, it has used real data on the work of the Central Bank of Iraq. Therefore, the results they will obtain are concrete results, And the problem of research may therefore be summarized by the following question: Has the Central Bank of Iraq been able to contribute to attracting foreign investment via its foreign reserves? To prove the main premise of the research, “there is a significant statistical relationship between the Central Bank of Iraq's foreign exchange reserves and foreign investment” the standard quantitative approach has been applied, and the research reached several conclusions, The relationship between the Iraqi Central Bank's foreign assets and foreign investment is positive, and this fits into the theoretical details of the research, which reflects the success of the goal of accumulating such reserves, especially since they increased in the period under discussion, It also reflects the success of the Central Bank of Iraq in managing these assets.